The evidence-based principles of VAC dressing applications; A review of the literature - Mafi, Reza; Malahias, Marco; Jordan, Daniel John; Hindocha, Sandip (International Journal of Infection Control, 2014)
Wound healing can be an uncomfortable and painful process that may at times lead to infection, hospitalisation and even death of the patient. Throughout the years, attempts have been made to make this process more manageable for patients, as well as clinicians. In 1993, negative pressure was first described with the intention of wound healing and by 1997 was being utilised in the clinical setting. The purpose of this literature review is to identify the available evidence for the use of vacuum assisted closure (VAC) therapy and the extent of its applications. A literature search of the online resources was undertaken and out of 212 articles and studies, 77 were found to match our inclusion criteria. VAC has been described as the preferred method of wound management (including in degloving injuries, infected sternotomy wounds, soft tissue injuries, open fractures of lower extremities, and diabetic foot ulcers) due to its ability to reduce healing time, help in prevention of infection and being cost-effective.